Performance analysis of a solar window incorporating a novel rotationally asymmetrical concentrator - Abu-Bakar, S.H.; Muhammad-Sukki, F.; Freier, D.; Ramirez-Iniguez, R.; Mallick, T.K.; Munir, A.B.; Mohd Yasin, S.H.; Mas'ud, A.A.; Bani, N.A. (Elsevier, 2016)
The race towards achieving a sustainable zero carbon building has spurred the introduction of many new technologies, including the BIPV (building integrated photovoltaic) system. To tackle the high capital cost of BIPV systems, LCPV (low-concentration photovoltaic) technology was developed. Besides the reduction of cost, the LCPV technology also produces clean energy for the building and promotes innovative architectural design. This paper presents a novel type of concentrator for BIPV systems. This concentrator, known as the RADTIRC (rotationally asymmetrical dielectric totally internally reflecting concentrator), was incorporated in a small double glazing window. The RADTIRC has a geometrical concentration ratio of 4.9069x. A series of experiments were carried out to evaluate the performance of the solar PV window both indoors and outdoors. It was found that the RADTIRC-PV window increases the short circuit current by 4.13x when compared with a non-concentrating solar PV window. In terms of maximum power generation, the RADTIRC-PV window generates 0.749 W at normal incidence, 4.8x higher than the non-concentrating counterpart.